(untitled) (Orfeu, 2021)
The present paper aims to investigate points of production of possible scenic senses from the musical orchestration of the opera Otello, to observe the orchestral articulation destined to create theatrical effects and, consequently, to generate poetic raw material to be available to future projects of staging of the mentioned lyrical drama or reflections on it. To do so, the investigation will be carried out with the analysis of the score and the libretto, confronting them with Boito’s original staging project and with the doctrine of ethos, the theory of affects and semiotics. The work is justified for some reasons: the shortage of proposals of this nature involving the Verdian work, in particular, Otello, in the Portuguese language; provide the study of music in connection with other arts; and because the study of the relations of the signs that compose the opera, even if coming from different artistic sources, enriches the process of pedagogy of this art.